Salvinia minima Baker (Salviniaceae): A new Pteridophytic record for Bangladesh - Shifa, Sabiha Alam; Alfasane , Md Almujaddade; Hassan , Md Abul (Bangladesh Journal of Plant Taxonomy, 2024)
Abstract not available Bangladesh J. Plant Taxon. 31(2): 321-323, 2024 (December)